Studi Analisis Tentang Kesulitan Membaca (Dyslexia) Serta Upaya Mengatasinya Pada Siswa Vb SD Muhammadiyah 22 Sruni, Surakarta - Feronika, Linda, Dra. Sri Hartini, SH, M.Pd (2016)
Education can be obtained anywhere, anytime and with anyone. One key to one's success in education is learning. The purpose of this study include the know: 1) To determine the factors that cause children have difficulty reading (dyslexia) in Class VB SD Muhammadiyah 22 Sruni, Surakarta, 2) To know the efforts made by teachers and parents to overcome reading difficulties ( dyslexia) students VB SD Muhammadiyah 22 Sruni, Surakarta. Types of Research based on a qualitative approach to the type of case study research. Collection Techniques dataadalah observation, interviews, and documentation. Results of the study: 1) Implementation of the learning activities in the classroom VB is already well underway. factors that cause difficulty in reading (dyslexia) on students including intelligence factors, socio-economic, overcrowded curriculum, teachers' expectations are too high does not match the child's abilities, and the attention and cooperation of parents is lacking. 2) Efforts to overcome reading difficulties (dyslexia) in the class VB, SD Muhammadiyah 22 Sruni namely, by providing additional tutoring and use of various methods vary. 3) Barriers to overcome reading difficulties (Dyslexia) in the class VB, SD Muhammadiyah 22 Sruni.yakni, parents of students who have difficulty reading (Dyslexia) in the class VB lack of attention to the development of children, motivation of students who have difficulty reading (Dyslexia) in the classroom VB to learn, practice and try still lacking, and the likely lack of school watching the students one by one.